Selection of Species with Soil Phytoremediation Potential After the Application of Protox-Inhibiting Herbicides - ALVES,C. (2018)
ABSTRACT: The objective of this work was to evaluate the phytoremediation potential of summer-grown species planted in soils contaminated with the herbicides fomesafen or sulfentrazone. In a greenhouse, doses of fomesafen (0.0, 0.125, 0.25 and 0.5 kg ha-1) and or sulfentrazone (0.0, 0.3, 0.6 and 1.2 kg ha-1), were applied in the pre-emergence of brown hemp, millet, velvet bean and sorghum. On the field, the recommended doses of fomesafen (0.250 kg ha-1) and sulfentrazone (0.600 kg ha-1) were used in the pre-emergence of brown hemp, velvet bean and sorghum, plus a treatment without cultivation. These species, before planting canola (bioindicator species), were submitted to mowing and burndown. In greenhouse trials, velvet bean, millet and sorghum tolerated fomesafen up to the recommended dose; sulfentrazone caused the total death of these plants. In the field experiments, the cultivation of velvet bean and brown hemp, in general, were the best alternatives preceding canola, in soil contaminated with fomesafen, and mainly velvet bean for sulfentrazone-contaminated areas. The number of siliques per plant of canola and its productivity were superior when using velvet bean as cover crop for both herbicides, regardless of the adopted management. It is possible to conclude that brown hemp and velvet bean were the species that best phytoremediated soils treated with fomesafen or sulfentrazone, and could be used in the decontamination of soils treated with these herbicides, regardless of the adopted management.